Assessing the Effectiveness of Pay-to-Go Policies: Evidence from Spain's Voluntary Return Program1. Issue 3 (September 2018) - Amuedo-Dorantes, Catalina; Pozo, Susan
Pay-to-go programs are incentive-based policies implemented by immigrant-receiving nations with the intention of enticing migrants home. Spain introduced such a program following its recent economic downturn. We assess its effectiveness using a difference-in-differences methodology. We test if the policy lowered the unemployment likelihood of eligible migrants by comparing changes in their propensity to be unemployed from before to after program implementation to changes experienced by similar non-eligible migrants. The Spanish pay-to-go policy did not entice immigrants to return home, except among Latin Americans, who enjoyed statistically and economically significant reductions in their unemployment likelihood following program implementation.